Pedro Peláez, Leader of the Filipino Clergy - Blanco, Roberto; Prado, Renan; Aguilar, Filomeno (2010)
This article provides new information on the creole Filipino, Fr. Pedro Pablo Peláez, who, together with Fr. José Burgos, was the most outstanding clergyman in the nineteenth-century Philippines. It discusses Father Peláez’s previously unknown activities in the cabildo of the Manila Cathedral, where he was its most distinguished member. It analyzes his reformist ideas and explains his work and strategy to defend the Filipino secular clergy, whose rights were being violated by the royal orders of 1848 and 1861. Against the reactionary religious orders, Peláez had a detailed modus operandi to defend the legitimacy of native priests’ control of parishes. Although his activities were cut short by his unexpected death in the earthquake of June 1863, Peláez served as an inspiration to be emulated.
Keywords: Pelaez, Pedro Pablo, 1812-1863; Priests; Secularization (Theology); Secularization